Acute Disseminated Encephalomyelitis: A case series and review of literatures - Mohammad Sadegh Rezai; Mehrdad Taghipour; Fariborz Azizi; Ali Abbaskhanian (Mazandaran University of Medical Sciences, 2013)
Abstract Acute disseminated encephalomyelitis (ADEM) is a rare immune mediated and demyelinating disease of the central nervous system that usually affects children. It as a monophasic disorder related with multifocal neurologic symptoms. Here in this paper we report seven cases of ADEM in pediatrics and besides a review of literatures are presented.